Bifunctional imidodiphosphoric acid‐catalyzed controlled/living ring‐opening polymerization of trimethylene carbonate resulting block, α, ω‐dihydroxy telechelic, and star‐shaped polycarbonates. Issue 7 (27th December 2013) - He, Xiaojiang; Ji, Yufeng; Jin, Yu; Kan, Suli; Xia, Haidong; Chen, Jia; Liang, Bingqi; Wu, Hao; Guo, Kai; Li, Zhenjiang
ABSTRACT The ring‐opening polymerization (ROP) of trimethylene carbonate (TMC) using imidodiphosphoric acid (IDPA) as the organocatalyst and benzyl alcohol (BnOH) as the initiator has been investigated. The polymerization proceeded without decarboxylation to afford poly(trimethylene carbonate) (PTMiC) with controlled molecular weight and narrow polydispersity. 1H NMR, SEC, and MALDI‐TOF MS measurements of the obtained PTMC clearly indicated the quantitative incorporation of the initiator at the chain end. The controlled/living nature for the IDPA‐catalyzed ROP of TMC was confirmed by the kinetic and chain extension experiments. A bifunctional activation mechanism was proposed for IDPA catalysis based on NMR and FTIR studies. Additionally, 1, 3‐propanediol, 1, 1, 1‐trimethylolpropane, and pentaerythritol were used as di‐ol, tri‐, and tetra‐ol initiators, producing the telechelic or star‐shaped polycarbonates with narrow polydispersity indices. The well‐defined diblock copolymers, poly(trimethylene carbonate)‐block‐poly(δ‐valerolactone) and poly(trimethylene carbonate)‐block‐poly(ε‐caprolactone), have been successfully synthesized by using the IDPA catalysis system. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 1009–1019